2010
DOI: 10.3945/jn.109.112912
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating LDL Phenol Levels in Men Who Consumed Virgin Rather Than Refined Olive Oil Are Associated with Less Oxidation of Plasma LDL ,

Abstract: In human LDL, the bioactivity of olive oil phenols is determined by the in vivo disposition of the biological metabolites of these compounds. Here, we examined how the ingestion of 2 similar olive oils affected the content of the metabolic forms of olive oil phenols in LDL in men. The oils differed in phenol concentrations as follows: high (629 mg/L) for virgin olive oil (VOO) and null (0 mg/L) for refined olive oil (ROO). The study population consisted of a subsample from the EUROLIVE study and a randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
4
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 58 publications
5
69
4
6
Order By: Relevance
“…In a human study, plasma oxidized LDL concentrations were negatively correlated with the phenol content of LDL in men who ingested different olive oils. 66 Because PON1 prevents oxidation of LDL, lower oxidized LDL concentrations might be due to PON1 induction.…”
Section: Bayram Et Almentioning
confidence: 99%
“…In a human study, plasma oxidized LDL concentrations were negatively correlated with the phenol content of LDL in men who ingested different olive oils. 66 Because PON1 prevents oxidation of LDL, lower oxidized LDL concentrations might be due to PON1 induction.…”
Section: Bayram Et Almentioning
confidence: 99%
“…The presence of these compounds in LDL strengthens claims that these compounds can act as in vivo antioxidants. The effect of the intake of virgin and refined olive oils after long-term ingestion of real-life doses on the content of the metabolites in LDL was examined as well (de la Torre-Carbot et al, 2010). The phenols in VOO modulated the LDL content of 3 phenolic metabolites, Hyty, Ty, and HVA sulfates; the concentration of these compounds increased significantly after the ingestion of VOO, in contrast to the refined one.…”
Section: Binding Of Olive Oil Polyphenols To Lipoproteinsmentioning
confidence: 99%
“…Determination and quantification of the biological metabolites of olive oil polyphenols in HDL were performed by means of High Performance Liquid Chromatography associated with mass spectrometry, following previously described methodology (5).…”
Section: Determination Of Biological Metabolites Of Olive Oil Polyphementioning
confidence: 99%
“…3,4 Previous results from our group showed that olive oil polyphenols increased dose dependently high-density lipoprotein (HDL) cholesterol levels. 3 Although it has been widely reported that low HDL cholesterol levels are strongly associated with high cardiovascular risk, 5 recent data indicate that increased HDL cholesterol levels do not imply a reduction in the risk of experiencing a myocardial infarction. 6 A key objective in cardiovascular disease prevention strategies should, therefore, be not only to increase HDL cholesterol but also to enhance its biological function.…”
mentioning
confidence: 99%